2016
DOI: 10.1088/0034-4885/79/11/110001
|View full text |Cite
|
Sign up to set email alerts
|

A review on locomotion robophysics: the study of movement at the intersection of robotics, soft matter and dynamical systems

Abstract: Discovery of fundamental principles which govern and limit effective locomotion (self-propulsion) is of intellectual interest and practical importance. Human technology has created robotic moving systems that excel in movement on and within environments of societal interest: paved roads, open air and water. However, such devices cannot yet robustly and efficiently navigate (as animals do) the enormous diversity of natural environments which might be of future interest for autonomous robots; examples include ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
192
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 235 publications
(203 citation statements)
references
References 282 publications
3
192
0
Order By: Relevance
“…[13] and many others [3,12,[14][15][16][17][18], the initial impact forces are consistently larger than expected from Poncelet drag or similar drag models, which is sometimes attributed [12] to a shock wave at impact [19]. These large forces are short lived but may be most important for determining damage to the grains and projectile [3,20] and for capturing the dynamics of a highly transient process like a jumping animal or robot [5,6]. However, there is currently no theory that captures these initial forces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13] and many others [3,12,[14][15][16][17][18], the initial impact forces are consistently larger than expected from Poncelet drag or similar drag models, which is sometimes attributed [12] to a shock wave at impact [19]. These large forces are short lived but may be most important for determining damage to the grains and projectile [3,20] and for capturing the dynamics of a highly transient process like a jumping animal or robot [5,6]. However, there is currently no theory that captures these initial forces.…”
mentioning
confidence: 99%
“…We find that the early-stage forces are inherently related to wave propagation, but the current theory of shocks in granular media cannot capture them, suggesting that a new theory is needed. The insensitivity of our results to many system details suggest that they may also apply to impacts into similar materials like foams and emulsions.High-speed impact by an intruder into a granular bed is a ubiquitous process with broad relevance in many disciplines, including ballistics [1-4], robotics [5,6], astrophysics [7], and earth science [8]. The forces exerted by the grains on the intruder are often described using Poncelet drag, which is dominated by a velocity-squared force with a nearly constant drag coefficient [9][10][11][12].…”
mentioning
confidence: 99%
“…Mobile robots generally can move either by using wheeled mechanisms, like technology for vehicles, or by using articulated legs, the simplest of the biological approaches to locomotion [7]. In general, legged locomotion requires higher degrees of freedom when compared with wheeled locomotion and therefore greater mechanical complexity.in additi on to being simple; it is suitable very well to the flat ground.…”
Section: Implementation Of Controlled Robot For Fire Detection and Exmentioning
confidence: 99%
“…Abstracting from animal models, one may ask conversely to which extent compliant locomotion may be generated via self-organizing principles [10], that is in the absence of top-down control in the form of a central pattern generator. One talks in this context of 'embodiment' [11], when part of the computation generating locomotion is carried out by the elasto-mechanical properties of the constituting body [12]. For quadruped robots with legs that are independently controlled by single non-linear phase oscillators [13], it has been shown that the limb-specific sensorimotor feedback derived form pressure sensors leads to self-organized interlimb communications, with emerging gaits that correspond to walking, trotting and galloping [14].…”
Section: Introductionmentioning
confidence: 99%